Guatemala : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report on the Observance of Standards and Codes (ROSC) provides an assessment of Guatemala's macroeconomic statistics against the General Data Dissemination System complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that the legal framework for statistical activity is broadly adequate, and institutions display a commitment to disseminate macroeconomic statistics, largely through the Internet. However, there is scope to improve the methodological basis and source data underpinning most datasets, as well as the mix and level of resources in a few cases.